The lion, the witch and the wardrobe - Lewis, C. S. (Clive Staples), 1898-1963. (New York, NY : Macmillan, 1977)
Four English school children find their way through the back of a wardrobe into the magic land of Narnia and assist Aslan, the golden lion, to triumph over the White Witch, who has cursed the land with eternal winter.
Keywords: Large type books; Narnia (Imaginary place) -- Fiction; Large type books; Fantasy fiction